Cornelius Gurlitt and the Treatment of Diocletian's Palace in Split - Špikić, Marko (2012)
The problem of treatment of historical monuments in Europe reached its peak at the beginning of the 20th century. After several decades of fervent discussions and polemics on the proper method of treatment, initiated by Ruskin’s critique of stylistic restoration in his Lamp of Memory, there appeared in fin-de-siècle Central Europe and Italy a new approach to conservation promoting keywords such as Pflege, Erhaltung, conservazione, and manutenzione. As is well known, it had its protagonists in the eminent art history scholars and architects such as Boito, Thausing, Riegl, Dehio, Dvořák, Giovannoni and Gurlitt. At the beginning of the 20th century Cornelius Gurlitt was one of the leading promoters of the modern cult of monuments in Germany, participating at the conferences Tage der Denkmalpflege since their beginning in Dresden in 1900. His discussions and critiques of Viollet-le-Duc’s principles are well documented, while the minutes of the German conferences establish him as one of the pioneers of the motto Konservieren, statt restaurieren! Thanks to his visit to Zagreb in 1908, where he held a lecture on the founding of the cities, Gurlitt has been referenced in Croatian historiography of art and conservation. This paper explores Gurlitt’s connections with Split and his perception of Diocletian’s Palace in the context of the discussions on sventramenti and isolamenti, on one hand, and conservation of Stimmung and picturesqueness of the heterogeneous monumental complex, on the other.
Projekt MZOS
ENG